A FUNÇÃO COESIVA DOS PRONOMES RELATIVOS NOS HIPERTEXTOS DA REDE SOCIAL FACEBOOK - JARDIM, Eveline dos Santos (2020)
The present study aim is the relative pronouns paper in hypertexts social Facebook as a responsible fact for the continuing semantics information established in textuality development. Text meaning is built along linguistic elements expressed in the text itself, gaining hypertexts material form, as the relative pronoun. The main authors who give support to our theory survey are among others: Antunes (2005), Arnauld and Lancelot (2001), Cavalcante (2011, 2012, 2013, 2014), Costa Val (1994), Chizzoti (2016), Favero (1991), Koch (2002, 2009, 2017, 2018), Lèvy (1993, 1999), Marcuschi (2008, 2012), Shepherd and Saliés (2013), Barton and Lee (2015). The methodology procedures are of qualitative basis, using in Merleau-Ponty (2006) Phenomenology Perception the inquiry reality understanding path. For the collecting data-base we built a “corpus” consisting of 60 (sixty) hypertext excerpts from social Facebook. From that “corpus”, we selected 16 (sixteen) hypertexts to identify them as research subject description. Those hypertexts were analysed a under the following methodology procedures: a) ideography analysis – starting analysis of each text identifying unit meaning and synthesis of each description; b) nomotectics analysis – when you join together analysed descriptions in order to identify open categories, also known as analysis categories. Then, three open categories were identified: Subject Referential Expression Paper, Verbal Complement Referential Expression Paper and Clause Introducer Referential Paper. Those categories were interpreted under the understanding of methodology theory basis that gave support to a research and made it possible to reveal important insights on the phenomenon we studied that we believe can open new useful way to future researches and some profitable and advanced studies in linguistic open to useful changes, especially with regards to text linguistic in the digital cyberspace with people in the web. These elements can also contribute to increase studies about textuality and their meaning coming out of interaction on historic, social and collective knowledge.